Eco-Friendly Synthesis of Ag Nanoparticle-Based Antibacterial Agents Using Tamarindus indica Extract as a Bioreductant - Firza Sofia Balqis; ST. Ulfawanti Intan Subadra; Muhammad Safwan bin Abd Aziz; Ahmad Taufiq; Arif Hidayat (JST (Jurnal Sains dan Teknologi), 2026)
Currently, the whole world is concerned about diseases caused by pathogenic bacteria because they can be fatal if not treated immediately. Therefore, a strategy is needed to prevent bacterial growth, including the development of new antibacterial agents. This study aims to develop Ag nanoparticles (AgNPs) using the bioreductant Tamarindus indica extract as an antibacterial agent. This study includes laboratory experimental research. The experiment began with preparing Tamarindus indica extract, followed by the preparation of AgNPs using the coprecipitation method. The successful formation of AgNPs was confirmed by XRD, which showed an FCC structure with a crystal size of 32.63 nm and a lattice parameter of 4.08 Å. Furthermore, the FTIR spectrum also confirmed the presence of the main functional group of AgNPs, namely Ag–O. In addition, the EDX results also confirmed the presence of an Ag energy peak from AgNPs. AgNPs have a morphology in the form of spherical particles with an average size of 45.55 nm. The antibacterial agent performance of AgNPs has been tested using the well diffusion method. The analysis results showed that AgNPs have inhibition zone diameters of 12.98, 14.44, 13.64, and 18.98 mm for Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa, respectively. These results indicate that AgNPs using Tamarindus indica extract as a bioreductant exhibit good antibacterial activity and could serve as an alternative, environmentally friendly antibacterial agent.